2019
DOI: 10.1590/s1679-87592019022706701
|View full text |Cite
|
Sign up to set email alerts
|

Dredging impact on trace metal behavior in a polluted estuary: a discussion about sampling design

Abstract: Dredging impact on trace metal behavior in a polluted estuary: a discussion about sampling design Studies involving coastal sediment resuspension have shown that trace metals could be released to the water column due to changes in physical-chemical conditions. Therefore, if environmental agencies adopt screening protocols with insufficient evaluations of contaminant mobilization risks for a given area, the prediction of environmental impacts caused by dredging may be limited. This work evaluates the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…In the aquatic environment, Zn occurs mainly in the form of Zn +2 , the ion shows affinity with organic matter, Fe and Mn oxides and hydroxides, and the fine fraction (Fonseca et al, 2013). In this study, Zn was positively correlated with TOC, Fe, Mn, and clay in both bays, as reported in previous studies in Guanabara Bay and Sepetiba Bay, which found similar correlations [18,32,40,42].…”
Section: Sediment Quality Guidelines and Adverse Effect Indexsupporting
confidence: 89%
See 3 more Smart Citations
“…In the aquatic environment, Zn occurs mainly in the form of Zn +2 , the ion shows affinity with organic matter, Fe and Mn oxides and hydroxides, and the fine fraction (Fonseca et al, 2013). In this study, Zn was positively correlated with TOC, Fe, Mn, and clay in both bays, as reported in previous studies in Guanabara Bay and Sepetiba Bay, which found similar correlations [18,32,40,42].…”
Section: Sediment Quality Guidelines and Adverse Effect Indexsupporting
confidence: 89%
“…Guanabara Bay is a eutrophicated environment [8,20,26,32], and in this type of environment, one of the main complexants of metals is organic matter [20,26,27]. The organic carbon reduces the solubility and toxicity of metals [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in the port basins, sediments can also represent a collector for PTEs [3,4] and a secondary source of PTEs due to their handling during dredging activities or resuspension during vessel manoeuvres. In fact, in these cases, sediment movements can promote elements dissolution and transfer in the water column [5]. Despite the numerous PTEs inputs, the rate of port seawater contamination by PTEs is difficult to evaluate because ports are open systems, and toxic elements tend to be very diluted in the water column.…”
Section: Introductionmentioning
confidence: 99%